Bifurcation and lyapunov exponent in orthogonal frequency division multiplexing - Suansook, Yoothana; Paithoonwattanakij, Kitti (My University, 2008)
In this paper we have review the effective transmission technique called Orthogonal Frequency Division Multiplexing (OFDM) that use in high-speed bidirectional wireless data transfer and mobile data transfer. We have presented the bifurcation diagram and divergence rate of the function that arises in transmission technique the sinc function. The parameters are nonlinear indicators that explained how nonlinear system changes from periodic to chaotic behavior. Bifurcation diagram of the system is characterized when the system can exhibit the chaotic behavior. The Lyapunov exponent is characterized the divergence rate of dynamical system. © 2008 IEEE.